Blue photoluminescence enhancement achieved by zero-dimensional organic indium halides via a metal ion doping strategy. (24th November 2022) - Lin, Fang; Yu, Guicheng; Weng, Shuchen; Zhou, Chao; Han, Yonglei; Liu, Wei; Zhou, Kang; Wang, Yongfei; Lin, Haoran
Abstract : PLQE enhancement and emission manipulation have been achieved for zero-dimensional (MA)4 InCl7 through a metal ion doping strategy. Cs + or Mn 2+ doping result in defect passivation and homogeneous crystals, while Sb 3+ doping shift the emission center. Abstract : Low-dimensional organic–inorganic metal halide hybrids exhibit promising optical properties for light emitting applications. However, developing lead-free blue-light emitters with high photoluminescence quantum efficiency (PLQE) remains an ongoing challenge. In our work, a novel zero-dimensional (0D) indium hybrid compound (MA)4 InCl7 (MA = CH3 NH3 + ) was developed which exhibited broadband blue emission with a PLQE of 11.2% when excited by ultraviolet (UV) light. More interestingly, upon Cs + or Mn 2+ doping, the emission of the 0D compound further blue-shifted and became narrower, while the PLQE was significantly enhanced to 18.8% (Cs + ) or 20.7% (Mn 2+ ). More prominent PLQE enhancement to 74.7% was observed after Sb 3+ doping, which also altered the emission spectrum to the orange region. According to experimental characterization and theoretical calculations, we attribute the PLQE enhancement upon Cs + and Mn 2+ doping to defect passivation and the orange emission upon Sb 3+ doping to altered emission centers. We have demonstrated that multiple metal ions possess the ability to improve the light emitting properties of 0D organic–inorganic metal halides, and (MA)4 InCl7 could be utilized as a Sb 3+ heavy metal ion sensor with high selectivity and sensitivity.